Pelatihan Penyusunan Desain Praktikum dan Penggunaan KIT Praktikum IPA Bagi Guru IPA SMP Di Kabupaten Serang - Pursitasari, Indarini Dwi; Permanasari, Anna; Rubini, Bibin; Ardianto, Didit; Heliawati, Leny; Nulhakim, Lukman; Kurniasih, Septi; Taufik, Annisa Novianti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Science learning in several schools in the Serang district still rarely conducts practicum, although practicum kits are available. Therefore, it is necessary to train teachers who are members of the Science MGMP Serang District. The purpose of the activity is to improve the skills of teachers to design simple practicums and use practicum kits. Activities were carried out in the duration of 34 JP in the form of training and assignment activities. Training session 1 was conducted online with output in the form of practicum designs made by teachers, while session 2 training was carried out offline at SMP Negeri 1 Ciruas. Academic evaluation is carried out on the collected tasks and non-academic evaluation includes participants' responses to training activities. The data obtained were analyzed in a quantitative descriptive manner. The results of the activity showed that teachers had varied teaching experiences, and the number of assignments collected was 40 practicum designs. Teachers are skilled in drafting practicum designs and using kits well. Teachers are satisfied with the training activities and hope that the activities can be carried out sustainably. After the activity, teachers are expected to be able to apply the knowledge and skills they have gained to carry out practicum activities in learning science at their respective schools